Assessment of Autopsied Deaths due to Firearms Between 2010-2012 in Elazığ - Türkoğlu, Abdurrahim; Tokdemir, Mehmet; Tunçez, Ferhat Turgut; Börk, Turgay; Yaprak, Burhan; Şen, Mustafa (The Bulletin of Legal Medicine, 2014)
The rate of deaths due to firearms is gradually increasing in our country and worldwide. Considering all medicolegal deaths, deaths due to firearms constitute a significant proportion. The purpose of our study is to determine general characteristics of death cases due to firearms and to compare them with similar studies. 120 cases (14.3%) who were determined to be died due to firearms out of 838 cases that were undergone death examination and autopsy between 2010-2012 in Fırat University Hospital, Department of Forensic Medicine in Elazig were retrospectively evaluated. These cases were assessed based on the parameters such as age, sex, origin, type of gun used, shooting distance, number of entry, localization of wound, place of event and time of the event. 102 (85%) of the cases were men and 18 (15%) were women. Mean age was 31.58±14.34, including 9 years as the youngest and 86 as the oldest. It was observed that deaths occurred within 20-29 age group (45.8%), during May (14.2%) and summer (30.8%) more often. While the most frequent origins were terror (32.2%) and suicide (32.2%), other reasons were murder (27.3%) and accidental death. It was also observed that 81 of the cases (66.1%) had single entry hole and deaths were mostly due to head-neck injury (37.5%). Deaths due to firearms constitute an important part of criminal deaths occurring in our region. When compared with the data from Turkey and the world, some differences associated with regional factors are observed such as terror and sociocultural characteristics. We suggest that use of unlicensed guns should be avoided, special care should be given to medical examination and licensing criteria before the issue of gun licences and society should be educated in order to decrease death rates due to firearms. Key words: Firearm injury, autopsy, suicide